Kenya : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
KEY ISSUES Context: Kenya has embarked on major reforms in line with the 2010 constitution. The new government has started the process of devolution at a fast pace, introducing a reporting framework that allows for monitoring progress and challenges. Macroeconomic stability in a market-friendly environment continues attracting the interest of foreign investors. Kenya placed its first USD 2 billion Eurobond at favorable terms, with proceeds to be used to upgrade power generation and transportation. Promising commercial prospects of oil discoveries have the potential of providing significant foreign exchange and fiscal resources. Kenya is actively participating in the integration of East Africa, showing progress in reducing delays from the port of Mombasa to Kampala and Kigali. Kenyan banks export their successful business models through East Africa and other countries in the region, while complying with upgraded prudential regulations. The Central Bank of Kenya (CBK) maintains proactive financial inclusion policies that have been effective in facilitating access to credit by small and medium enterprises. Thanks to legal reforms, the Financial Action Task Force has removed Kenya from its watch list. Recent terrorist attacks and threats have raised security concerns, especially in coastal areas bordering Somalia. Outlook and policies: Growth is projected to accelerate to 5.8 percent in 2014/15 on the back of higher public and private investment and measures to improve the business environment. The 2014/15 budget aims at rebalancing recurrent and development spending. Medium-term fiscal policies intend to bring down the debt burden consistent with the East African Community Monetary Union (EAMU) Protocol convergence criteria. Inflation remains broadly in check, but rising food prices and rapid credit growth require careful monitoring by the CBK. Focus: Discussions centered on the implementation of devolution, in particular on the enforcement of accountability provisions. Some checks and balances are proving effective, such as the required Treasury approval of guarantees for county borrowing. However, a more systematic framework is needed. Staff and the authorities agreed that the scale of transfers to counties magnified government's cash management problems that need to be addressed with the help of the recently introduced Treasury Single Account (TSA). This would also contribute to more effective monetary operations. Discussions also focused on the design of the legal framework for natural resource management aimed at ensuring consistency with public finance management provisions.